2020
DOI: 10.1002/jum.15366
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Printed Model Fabrication and Effectiveness Evaluation in Fetuses With Congenital Heart Disease or With a Normal Heart

Abstract: Objectives-The purpose of this study was to investigate the technical feasibility and accuracy of applying 3-dimensional (3D) printing of normal and abnormal fetal hearts based on spatiotemporal image correlation (STIC) volume-rendered data. Methods-Spatiotemporal image correlation volume images of 15 healthy fetuses and 15 fetuses with cardiac abnormalities were collected, and Mimics software (Materialise NV, Leuven, Belgium) was used to postprocess the volume data to obtain a 3D digital model of fetal heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…Mowers et al compared a 2D echo with digital 3D models and 2D echo with printed 3D models, and showed a difference of 0.0 mm and 0.3 mm, respectively [26]. Other studies showed a strong correlation between 3D models and digital images but did not report the mean differences [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Mowers et al compared a 2D echo with digital 3D models and 2D echo with printed 3D models, and showed a difference of 0.0 mm and 0.3 mm, respectively [26]. Other studies showed a strong correlation between 3D models and digital images but did not report the mean differences [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…9 In comparison with CT and MRI, 3DUS is a safe, accessible, widely used, and preferred technique for prenatal diagnosis, and it is increasingly used for 3D printing. Several studies have mainly focused on cleft lip and palate 11,13 and congenital heart disease (CHD)s 15,16 in this regard. To show the deformities in different parts, MRI or CT was supplemented for a better view and diagnostic clarification.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is valuable by providing an in vitro individual model to study alternations in flow dynamics in challenging heart defects as well as for parents to understand the complexity of cardiac anomaly [ 114 ]. Even a spatiotemporal image correlation (STIC) technology to display the spatial structure of the fetal heart seen on 2D screens does not provide as much information as a physical 3D-printed model [ 115 ].…”
Section: Discipline Specific Applicationsmentioning
confidence: 99%